2005
DOI: 10.1021/jm050033v
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antipicornavirus Activity of 1-[5-(4-Arylphenoxy)alkyl]-3-pyridin-4-ylimidazolidin-2-one Derivatives

Abstract: A series of pyridylimidazolidinone derivatives was synthesized and tested in vitro against enterovirus 71 (EV71). On the basis of compound 33 (DBPR103), introduction of a methyl group at the 2- or 3-position of the linker between the imidazolidinone and the biphenyl resulted in markedly improved antiviral activity toward EV71 with IC(50) values of 5.0 nM (24b) and 9.3 nM (14a), respectively. Increasing the branched chain to propyl resulted in a progressive decrease in activity, while inserting different hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…7) of the linker spacer between the imidazolidinone and biphenyl substantially improved the activity against EV71. 126 The (S)-(þ) enantiomer (EC 50 ¼ 3 nM) was 10-fold more potent against EV71 than the (R)-(À) enantiomer. 128 Furthermore, replacement of the chlorophenyl ring in this molecule (compound 14a) with the oxadiazole ring or the tetrazole ring resulted in dramatically improved inhibitory activity.…”
Section: F Pyridyl Imidazolidinonesmentioning
confidence: 99%
“…7) of the linker spacer between the imidazolidinone and biphenyl substantially improved the activity against EV71. 126 The (S)-(þ) enantiomer (EC 50 ¼ 3 nM) was 10-fold more potent against EV71 than the (R)-(À) enantiomer. 128 Furthermore, replacement of the chlorophenyl ring in this molecule (compound 14a) with the oxadiazole ring or the tetrazole ring resulted in dramatically improved inhibitory activity.…”
Section: F Pyridyl Imidazolidinonesmentioning
confidence: 99%
“…The inhibitors bind into the hydrophobic pocket within VP1 with high affinity and therefore cannot be dislodged upon receptor binding. Several putative capsidbinding inhibitors of EV71 were synthesized and shown to be effective (34,35), but molecular details of their interactions with the capsid proteins were not known.…”
mentioning
confidence: 99%
“…Although the V192M mutant exhibited poorer susceptibility to these three compounds in comparison with wild type and the other mutant EV71 viruses, it could be inhibited to 50% with 5.5 lM BPROZ-101 and 10.679 lM BPROZ-161, respectively. Antiviral activity of pyridyl imidazolidinones with different substitutions at the central position of the hydrophobic linker From our previous work, we found that the introduction of a methyl group at the central position of the linker between the imidazolidinone and the biphenyl groups (BPROZ-033) resulted in markedly improved antiviral activity [6]. The methyl group may contribute to the hydrophobic interactions between the compound and the VP1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Data was analyzed by using GraphPad Prism 4.0 software Chemical compounds Eleven modified pyridyl imidazolidinones were synthesized and used as chemical probes for antiviral assays. The synthesis methods for theses compounds have been described previously [6,7,9,33]. The chemical names for these compounds follow.…”
Section: Cytotoxicity Of Pyridyl Imidazolidinones On Rd Cellsmentioning
confidence: 99%
See 1 more Smart Citation